Oxaliplatin plus fluoropyrimidines as adjuvant therapy for colon cancer in older patients: A subgroup analysis from the TOSCA trial. (May 2021) - Rosati, Gerardo; Lonardi, Sara; Galli, Fabio; Di Bartolomeo, Maria; Ronzoni, Monica; Zampino, Maria G.; Banzi, Maria; Zaniboni, Alberto; Pasini, Felice; Bozzarelli, Silvia; Garattini, Silvio K.; Ferrari, Daris; et al.
Abstract: Background: Previous studies on oxaliplatin and fluoropyrimidines as adjuvant therapy in older patients with stage III colon cancer (CC) produced conflicting results. Patients and methods: We assessed the impact of age on time to tumour recurrence (TTR), disease-free survival (DFS), cancer-specific survival (CSS), and overall survival (OS) in 2360 patients with stage III CC (1667 aged <70 years and 693 ≥ 70 years) randomised to receive 3 or 6 months of FOLFOX or CAPOX within the frame of the phase III, TOSCA study. Results: Older patients compared with younger ones presented more frequently an Eastern Cooperative Oncology Group performance status equal to 1 (10.5% vs 3.3%, p < 0.001), a greater number of right-sided tumours (40.9% vs 26.6%, p < 0.001), and were at higher clinical risk (37.2% vs 33.2%, p = 0.062). The treatments were almost identical in the two cohorts (p = 0.965). We found a greater proportion of dose reductions (46.7% vs 41.4%, p = 0.018), treatment interruptions (26.1% vs 19.3%, p < 0.001) and a higher proportion of recurrences (24.2% vs 20.3%, p = 0.033) in the older patients. The multivariable analysis of the TTR did not indicate a statistically significant effect of age (hazard ratio [HR]: 1.19; 95% confidence interval [CI]: 0.98–1.44; p = 0.082). The HR comparing older with younger patients was 1.34 (95% CI: 1.12–1.59; p = 0.001) for DFS, 1.58 (95% CI: 1.26–1.99; p < 0.001) for OS, and 1.28 (95% CI: 0.96–1.70; p = 0.089) for CSS. Conclusions: Worse prognostic factors and reduced treatment compliance have a negative impact on the efficacy of oxaliplatin-based adjuvant therapy in older patients. Highlights: The outcome of oxaliplatin as an adjuvant therapy in elderly patients with colon cancer is doubt. Worse prognostic factors and reduced compliance have a negative impact on its effectiveness. Fluoropyrimidine monotherapy is an appropriate choice for most elderly patients. Only fit elderly patients should receive oxaliplatin as an adjuvant therapy.